2007
DOI: 10.1007/s11859-007-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Query translation on the fly in Deep Web integration

Abstract: Abstract:To facilitate users to access the desired information, many researches have dedicated to the Deep Web (i.e. Web databases) integration. We focus on query translation which is an important part of the Deep Web integration. Our aim is to construct automatically a set of constraints mapping rules so that the system can translate the query from the integrated interface to the Web database interfaces based on them. In this paper, we construct a concept hierarchy for the attributes of the query interfaces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, this sampling method requires improvement in many respects, such as the sampling independence, the flexibility of the parameters configuration and the integrity of the results that reflect the database content [13][14][15] In addition, these random sampling methods cannot ensure consistency between the sampling data and the WDB data, such as the consistency of keywords in text attributes, the consistency of numeric distribution in numerical attributes and the integrity of text attributes. Moreover, these methods do not consider the dependencies among attributes in the WDB.…”
Section: Related Workmentioning
confidence: 99%
“…However, this sampling method requires improvement in many respects, such as the sampling independence, the flexibility of the parameters configuration and the integrity of the results that reflect the database content [13][14][15] In addition, these random sampling methods cannot ensure consistency between the sampling data and the WDB data, such as the consistency of keywords in text attributes, the consistency of numeric distribution in numerical attributes and the integrity of text attributes. Moreover, these methods do not consider the dependencies among attributes in the WDB.…”
Section: Related Workmentioning
confidence: 99%
“…It was shown that the selected species of monocrystalline synthetic diamonds could be well dispersed in a pure aluminum-matrix. However, some ''microngrade'' diamond powders were particularly susceptible to the degradation during composite processing [6][7][8][9][10]. Natishan et al suggested that interfacial reaction in diamond/aluminum composites could be successfully suppressed by using a solid-state route, but the thermal conductivity was not addressed in this study [11].…”
Section: Introductionmentioning
confidence: 99%